Effectiveness of Tax Deduction at Source (TDS) in India - S.S. Murugan; Dr. S. Sekar (International Journal of Engineering and Management Research, 2019)
To Study and analyses all the purposes for which TDS in India was introduced to ensure whether they are properly achieved for collection of more revenues to Govt. Also study major types of tax system in the world. Study whether Adam smith’s all the four Canon of Taxation are satisfied by TDS mechanism and to what extent with reasons there for. To conclude, considering major tax collection mechanism, whether TDS mechanism is effective or not.